Aspirin Is Associated with Improved Survival in Severely Thrombocytopenic Cancer Patients with Acute Myocardial Infarction. (18th September 2017) - Feher, Attila; Kampaktsis, Polydoros N.; Parameswaran, Rekha; Stein, Eytan M.; Steingart, Richard; Gupta, Dipti
Abstract : Background: Patients with hematologic malignancies are at risk for severe thrombocytopenia (sTP). The risk and benefit of aspirin are not known in thrombocytopenic cancer patients experiencing acute myocardial infarction (AMI). Materials and Methods: Medical records of patients with hematologic malignancies diagnosed with AMI at Memorial Sloan Kettering Cancer Center during 2005–2014 were reviewed. sTP was defined as a platelet count <50, 000 cells per µL within 7 days of AMI. Results: Of 118 patients with hematologic malignancies who had AMI, 58 (49%) had sTP. Twenty‐five patients (43%) with sTP received aspirin as a treatment for AMI. Compared with patients without sTP with AMI, patients with sTP with AMI were less likely to receive aspirin (83% vs. 43%; p  = .0001) and thienopyridine treatment (27% vs. 3%; p  = .0005). During median follow‐up of 3.7 years after AMI, survival was lower in patients with sTP than in those with no sTP (23% vs. 50% at 1 year; log rank p  = .003). Patients with sTP who received aspirin for AMI had improved survival compared with those who did not (92% vs. 70% at 7 days, 72% vs. 33% at 30 days, and 32% vs. 13% at 1 year; log rank p  = .008). In multivariate regression models, aspirin use was associated with improved 30‐day survival both in the overall patient cohort and in sTP patients. No fatal bleeding events occurred. Major bleeding was not associated with sTP or aspirin use. Conclusion: Treatment of AMI with aspirin in patients with hematologic malignancies and sTP is associated with improved survival without increase in major bleeding. Abstract : In patients with hematologic malignancies and acute myocardial infarction with severe thrombocytopenia (platelet count < 50, 000 cells/mL), guideline‐recommended medical therapy is often withheld because of the fear of major bleeding. In this study, aspirin therapy was associated with improved survival without an increase in major bleeding in this high‐risk patient cohort.